O uso da WebQuest no ensino de física em uma turma do ensino médio, no contexto da educação pela pesquisa - Rodrigues, Alvori Vidal (2017)
The present dissertation aims to present the results of a research whose objective was to evaluate the contributions of the use of the WebQuest in the discipline of Physics in High School, in the context of educating by the research. This was done at a state education institute in the south of Brazil, with a group of high school students. For the accomplishment of this study a qualitative research was carried out, with data collection through questionnaire, field diary and production of materials carried out by the researched ones, supported by a bibliographical review. The method of analysis used was Discursive Textual Analysis (DTA). The results obtained point to an increase in students' motivation to learn Physics as a result of the interest aroused by the achievement of WebQuest produced from the reality of these students. It also points out the relationship between the layout of WebQuest as an organizer of research thinking, which generates aspects related to research education, with the reconstructive thinking being stimulated by this methodology, as well as the increase of cooperation and knowledge construction by the researched ones.